Outcome of 449 adult patients with rhabdomyosarcoma: an observational ambispective nationwide study - Emmanuelle Bompas; Loïc Campion; Antoine Italiano; Axel Le Cesne; Christine Chevreau; Nicolas Isambert; Maud Toulmonde; Olivier Mir; Isabelle Ray‐Coquard; Sophie Piperno‐Neumann; Esma Saada‐Bouzid; Maria Rios; et al. (Cancer Medicine)
Abstract Five‐year overall survival (OS) of localized RMS exceeds 70% in children (<18) but is very poor in adult patients. We analyzed the outcome and prognostic factors (PF) of a national series of adult patients with RMS in a large study. The study population consisted of two different cohorts: a retrospective cohort (157 adult patients treated in 13 reference centers between 05/1981 and 02/2010) and the prospective cohort (292 patients with RMS diagnosed and treated between 01/2010 and 12/2014 in France) included in the NetSarc database. A descriptive analysis of patients’ characteristics and prognostic factors was conducted on both series which were compared. In the retrospective series, histological subtypes were embryonal (E‐RMS) for 21% of patients, alveolar (A‐RMS) for 35% of patients, and “adult‐type” P‐RMS (pleomorphic, spindle cell RMS, not otherwise specified) (P) for 44% patients. This distribution significantly differed in the prospective cohort: A‐RMS: 18%; E‐RMS: 17%; and P‐RMS 65%. With a median follow‐up of 8.5 years, 5‐year OS for localized RMS and advanced RMS (with nodes and/or metastases) was 43% and 5%, respectively, (P < 0.0001), and median OS was 51, 33, and 16 months for E‐RMS, A‐RMS, and P‐RMS, respectively, in the retrospective cohort. The median OS was less than 40 months for the prospective nationwide cohort for the entire population. In a multivariate analysis of the retrospective study, independent prognostic factors for OS were A‐RMS, R0 resection, and adjuvant radiotherapy (RT). For localized RMS, age and use of pediatric chemotherapy (CT) regimen are independent prognostic factors. Adult patients with RMS have a poorer overall survival than pediatric patients, and survival varies considerably across histological subtypes.